A Repetitive Control Scheme for Harmonic Suppression of Circulating Current in Modular Multilevel Converters - He, Liqun; Zhang, Kai; Xiong, Jian; Fan, Shengfang (IEEE transactions on power electronics, 2015)
In a modular multilevel converter (MMC), the interaction between switching actions and fluctuating capacitor voltages of the submodules results in second- and other even-order harmonics in the circulating currents. These harmonic currents will introduce extra power loss, increase current stress of power devices, and even cause instability during transients. Traditional methods for circulating current harmonic suppression have problems such as limited harmonic rejection capability, limited application area, and complex implementation. This paper presents a plug-in repetitive control scheme to solve the problem. It combines the high dynamics of PI controller and good steady-state harmonic suppression of the repetitive controller, and minimizes the interference between the two controllers. It is suitable for multiple harmonic suppression, easy to implement, and applicable for both single-phase and three-phase MMCs. Simulation and experimental results on a single-phase MMC inverter proved the validity of the proposed control method.